1997
DOI: 10.1002/(sici)1098-2396(199702)25:2<125::aid-syn3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Depression of early and late monosynaptic inhibitory postsynaptic potentials in hippocampal CA1 neurons following prolonged benzodiazepine administration: Role of a reduction in Cl driving force

Abstract: GABAergic synaptic responses were studied by direct, monosynaptic activation of GABAergic interneurons in the CA1 region of in vitro hippocampal slices from rats made tolerant to the benzodiazepine, flurazepam. Monosynaptic IPSPs were elicited in CA1 pyramidal neurons, following 1 week oral flurazepam administration, by electrical stimulation at the stratum oriens/stratum pyramidale or stratum radiatum/ stratum-lacanosum border < or = 0.5 mm from the recording electrode plane. Excitatory input to pyramidal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Inhibitory pathways contributing to PPI in hippocampal slice have been well characterized and can involve both feed-forward and feed-back inhibitory circuits (Karnup and Stelzer 1999;Rogers and Hunter 1992;Turner 1990) with transmission via both GABA A and GABA B receptors. However, in the present study, the use of a 10-ms inter-pulse interval is selective for GABA A -versus GABA B -mediated events, because the latter exhibits a longer latency onset of response following an excitatory stimulus and is optimally observed with inter-pulse intervals of 200 ms (Davies et al 1990;Karlsson and Olpe 1989;Williams et al 1994;Zeng and Tietz 1997).…”
Section: Ppi In Ca1 Hippocampus-circuit Propertiesmentioning
confidence: 83%
“…Inhibitory pathways contributing to PPI in hippocampal slice have been well characterized and can involve both feed-forward and feed-back inhibitory circuits (Karnup and Stelzer 1999;Rogers and Hunter 1992;Turner 1990) with transmission via both GABA A and GABA B receptors. However, in the present study, the use of a 10-ms inter-pulse interval is selective for GABA A -versus GABA B -mediated events, because the latter exhibits a longer latency onset of response following an excitatory stimulus and is optimally observed with inter-pulse intervals of 200 ms (Davies et al 1990;Karlsson and Olpe 1989;Williams et al 1994;Zeng and Tietz 1997).…”
Section: Ppi In Ca1 Hippocampus-circuit Propertiesmentioning
confidence: 83%
“…Hypoxia/ischemia has been shown to increase intracellular chloride concentration in adult rat CA1 hippocampal neurons (Comerford et al, 2003; Inglefield and Schwartz-Bloom, 1998; Katchman et al, 1994; Mittmann et al, 1998) though the mechanism remains controversial. Changes in Cl− reversal potential in CA1 neurons were also seen after chronic BZ treatment, accompanied by GABA A R-mediated depolarization (Zeng et al, 1997). In our previous experiments, the resting membrane potential in cortical neurons at 13–15 days in vitro was around −65 mV (data not shown), hence the shift in chloride reversal potential from −59.5 ± 3.2 mV in control cells to −51.0 ± 3.1 mV recorded 24 h after hypoxia implies that GABA A R currents become significantly depolarizing after hypoxia and could increase neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…The discrete suppression of GABA A receptor function in CA1 pyramidal cells during prolonged flurazepam administration 47,73,[75][76][77][78] and the associated regionally localized, timedependent reductions in the expression of specific GABA A receptor subunit mRNAs 65,66 warranted quantitative immunohistochemical studies of selected hippocampal and cortical GABA A receptor subunit proteins (a1, a2, b1-3 and g2). Taken together with the findings of in situ hybridization studies, 65,66 the results of these quantitative immunohistochemical studies suggested that changes in the expression of specific GABA A receptor mRNAs (a1 and b3 subunits) were mirrored by changes in their respective subunit proteins.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,27,29,44,65,66,80,81 Such information may help to clarify the relationship between changes in protein expression (e.g., of a1, b2 and b3 subunits) and changes in the GABAergic function of some (CA1 pyramidal cells), but not other (CA3 pyramidal cells and dentate granule cells), hippocampal principal cell types in benzodiazepine-tolerant rats. 28,47,48,75,76,78 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation